Changes In The Financial System Stability Of Asean Founder Countries Due To Covid-19 - Rusiadi; Anwar Sanusi; Ade Novalina; Milenia M Tafonao; Audre Aprillia (International Journal of Science, Technology & Management, 2021)
The threat of the spread of coronavirus to economic growth and inflation in countries in the world will also seep into the global and domestic macrofinancial sector. This research was conducted to analyze how the level of change in the stability of the financial system of ASEAN Founders (ASEFO) with the emergence of the covid 19 pandemic. This study used secondary data (time series) in asefo countries. The model used is a different test model paired sample t-test. The results of the analysis showed that the Covid 19 pandemic had a significant effect on the stability of the financial system with the ASEFO State NPL indicator.